STRATEGI PEMASARAN DAN PERBAIKAN MUTU BERDASAR ANALISIS KEPUASAN KARYAWAN INSTANSI YANG BEKERJA SAMA DENGAN RS BETHESDA YOGYAKARTA = MARKETING AND QUALITY IMPROVEMENT STRATEGIES BASED ON ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Background: There are 115 institutions which are partners of Bethesda Hospital. For the hospital the partnership is a big opportunity to increase service utilization level provided and it can give reliable financial support. Some institutions or companies however do not continue the partnership. Objectives: The study aimed to identify the concurrence between expectation and performance perceived by employees of partner institutions of Bethesda Hospital. Additionally, it aimed to get information for quality improvement and marketing strategies of microservice system which could be adopted by the hospital. Methods: The study was of descriptive type which used cross sectional survey design through questionnaires (with 100 samples using proportional stratified sampling) and qualitative one through in depth interviews with decision makers of partner institutions (4 companies and 2 insurance companies using purposive sampling). Quantitative data analysis used Cartesius Diagram, where qualitative data used coding. Results: Aspects of patient (employee) satisfaction had the lowest percentage of concurence between expection and services as perceived by employees: which was 88.22% the lowest and 92.27% the highest. This belonged to good category. The concurence of 21 elements varied from 84.02%-97.31% which also belonged to good category. Based on distribution of Cartesius Diagram, aspects of convenience and cost should be improved whereas aspects of relationship between staff and patients and technical competence of staff should be sustained. Conclusion: Concurence of patient satisfaction elements varied from 84.02% 97.31% which belonged to good category. Elements of satisfaction which was put as first priority for improvement were doctors' availability and on time visit, cleanliness and tidiness of inpatient rooms, good lighting, quietness and transparent cost calculation. Information for input in marketing strategy compilation of micro service system induced improvement of service quality, competitive tariff, active communication with company clinical doctors and company managers through periodic information delivery. Keywords: patient satisfaction, marketing strategies, quality improvement